Law Enforcement Against Fraud and/or Embezzlement (Study of KSP Intidana Central Java, Indonesia) - Andryanto, Chandra (JILS (Journal of Indonesian Legal Studies), 2018)
Crime recognized as a form of act which opposing the humanity’s moral, harming people, has asocial nature, and violating law also criminal law. Because of that, crime must be eradicated, or must not let it continue until it evolves for the sake of discipline, security, and safety of people. One of the crimes that listed in criminal law (KUHP) is an act of fraud or embezzlement. The concept theory of this paper used the criminal sanctions which included: investigation, criminal act, the definition of scam or fraud, and the theories about cooperative. The paper indicated that the implementation of investigation process against perpetrator of fraud and/or embezzlement of Intidana Cooperative in Central Java’s Regional Police implemented after police report number: LP/B/426/XI/2015/Jateng/Reskrimum, November 5th, 2015 and Inquiry Warrant with number: 336b/XI/2015/Dit Reskrimum November 17th, 2015 also Investigative Warrant with number: 336a/XI/2015/DitReskrimum November 20th, 2015. The next step which the Police took is to call and inspect victims or witnesses, arrest of suspect, detention of suspects and seizure of evidence. The investigation process by the investigator and the assistant investigator begins by contacting the complainant and completing the initial investigation administration then conducting the inspection of witnesses and the collection of evidence, determining and seeking, conducting the suspect's examination by arrest and detention of the suspect. The dimensions of criminal law enforcement in the conduct of investigation on the perpetrators of criminal acts of fraud and/or embezzlement of the Intidana Cooperative in Central Java’s Regional Police is to minimize the occurrence of similar criminal acts, especially for the perpetrators in fraud and embezzlement cases in the future can be charged with criminal liability of fraud and embezzlement.